2017
DOI: 10.5500/wjt.v7.i4.243
|View full text |Cite
|
Sign up to set email alerts
|

De novo intraocular amyloid deposition after hepatic transplantation in familial amyloidotic polyneuropathy

Abstract: The familiar amyloid polyneuropathy (FAP) is a rare autosomal-dominant systemic amyloidosis. Amyloid deposition occurs more frequently and extensively in the vitq. The increase in intraocular pressure (IOP) is a result of deposition of transthyretin (TTR) in trabecular meshwork. Rarely, the amyloid deposition in anterior segment can be more exuberant than in posterior segment. A 42 years old man, with FAP (Val30Met mutation), liver transplantation in 1997. He was asymptomatic, without any significant ocular ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Liver transplantation slows disease progression and increases the survival rate among patients with hereditary ATTR amyloidosis 9,10 . However, as TTR is produced not just in the liver, but also in ocular tissues 11,12 , eyesight deterioration due to vitreous amyloidosis and secondary glaucoma, has become relatively common among patients with hereditary ATTR amyloidosis 6,9,13 .…”
mentioning
confidence: 99%
“…Liver transplantation slows disease progression and increases the survival rate among patients with hereditary ATTR amyloidosis 9,10 . However, as TTR is produced not just in the liver, but also in ocular tissues 11,12 , eyesight deterioration due to vitreous amyloidosis and secondary glaucoma, has become relatively common among patients with hereditary ATTR amyloidosis 6,9,13 .…”
mentioning
confidence: 99%
“…Furthermore, an increased lipid peroxidation, being the result of ROS-induced cell damage, was noticed as well as an impairment of metalloproteinases-2 (MMP-2) expression, resulting in an accumulation of extracellular matrix. This accumulation (i.e., plaques) in TM could be seen several years before by electron microscopy studies [77,78].…”
mentioning
confidence: 72%
“…It acts as a thyroxine and vitamin A transporter, and it carries retinol and in a lesser amount, thyroxine (T4) when mutated, its tetramer conformation turns into monomers that aggregate and form amyloid deposits [75,76]. The most serious ocular manifestation of FAP is glaucoma [76][77][78], and it has been suggested that the loss of peripheral nerve fibers in FAP, and the consequent ischemia, is caused by endoneurial amyloid deposits and the toxicity of amyloid deposits to TM cells [75].…”
Section: Trabecular Meshwork and Amyloidosismentioning
confidence: 99%
See 1 more Smart Citation